Genomics-driven Reconstruction of Acinetobacter NAD Metabolism: INSIGHTS FOR ANTIBACTERIAL TARGET SELECTION - Sorci, Leonardo (American Society for Biochemistry and Molecular Biology, 2010)
Enzymes involved in the last steps of NAD biogenesis, nicotinate mononucleotide adenylyltransferase (NadD) and NAD synthetase (NadE), are conserved and essential in most bacterial species and are established targets for antibacterial drug development. Our genomics-based reconstruction of NAD metabolism in the emerging pathogen Acinetobacter baumannii revealed unique features suggesting an alternative targeting strategy. Indeed, genomes of all analyzed Acinetobacter species do not encode NadD, which is functionally replaced by its distant homolog NadM. We combined bioinformatics with genetic and biochemical techniques to elucidate this and other important features of Acinetobacter NAD metabolism using a model (nonpathogenic) strain Acinetobacter baylyi sp. ADP1. Thus, a comparative kinetic characterization of PncA, PncB, and NadV enzymes allowed us to suggest distinct physiological roles for the two alternative, deamidating and nondeamidating, routes of nicotinamide salvage/recycling. The role of the NiaP transporter in both nicotinate and nicotinamide salvage was confirmed. The nondeamidating route was shown to be transcriptionally regulated by an ADP-ribose-responsive repressor NrtR. The NadM enzyme was shown to possess dual substrate specificity toward both nicotinate and nicotinamide mononucleotide substrates, which is consistent with its essential role in all three routes of NAD biogenesis, de novo synthesis as well as the two salvage pathways. The experimentally confirmed unconditional essentiality of nadM provided support for the choice of the respective enzyme as a drug target. In contrast, nadE, encoding a glutamine-dependent NAD synthetase, proved to be dispensable when the nondeamidating salvage pathway functioned as the only route of NAD biogenesis.